Identifying health conditions, priorities, and relevant multilevel health promotion intervention strategies in African American churches: A faith community health needs assessment. (April 2018) - Berkley-Patton, Jannette; Thompson, Carole Bowe; Bradley-Ewing, Andrea; Berman, Marcie; Bauer, Alexandria; Catley, Delwyn; Goggin, Kathy; Williams, Eric; Wainright, Cassandra; Petty, Therese; Aduloju-Ajijola, Natasha
Highlights: African American churches have many strengths to address health disparity issues. African American faith leaders were engaged in a health needs assessment (HNA). Diabetes and heart disease/stroke were identified as priority health issues. Important/feasible health promotion church intervention strategies were identified. A multilevel health promotion church intervention was designed from HNA findings.